The serum uric acid to apolipoprotein A1 ratio is independently correlated with metabolic dysfunction-associated steatotic liver disease in type 2 diabetes mellitus: findings from a single national metabolic management center cohort - Guo, Xiu Li; Tu, Mei; Qiu, Xiu Ping; Wang, Wei (Frontiers in Endocrinology, 2025)
BackgroundRecent evidence suggests that the serum uric acid to apolipoprotein A1 ratio (UAR) may be a novel biomarker for metabolic dysfunction-associated steatotic liver disease (MASLD). This study aims to investigate the relationship between UAR and MASLD, and compare the diagnostic ability of UAR with other insulin resistance-related markers for MASLD in individuals with type 2 diabetes mellitus (T2DM).MethodA cohort of 1,019 individuals with T2DM was recruited from the National Metabolic Management Center of our hospital. Unenhanced abdominal CT scans were performed to evaluate liver steatosis for diagnosing MASLD. The association between UAR and the risk of MASLD was analyzed using weighted binomial logistic regression, restricted cubic splines (RCS), and subgroup analysis. Receiver operating characteristic (ROC) curve analysis was conducted to compare the diagnostic performance of UAR with other insulin resistance-related markers, including the serum uric acid to high-density lipoprotein cholesterol ratio (UHR), triglyceride to high-density lipoprotein cholesterol ratio (THR), and triglyceride to apolipoprotein A1 ratio (TAR).ResultsParticipants in the MASLD group exhibited elevated UAR levels. After full adjustments for potential confounders, UAR remained independently associated with MASLD (OR: 1.65, 95% CI: 1.45-1.89, P < 0.001). Subgroup analyses revealed that this association was consistent across various subgroups, including sex, drinking status, hypertension, lipid-lowering therapy, and body mass index (P < 0.05). RCS analysis demonstrated a linear increase in the risk of MASLD with higher UAR levels (P for nonlinear = 0.319). ROC curve analysis indicated that UAR provided good diagnostic performance for MASLD (AUC:0.777, 95% CI: 0.749- 0.805), comparable to TAR (AUC difference: -0.003, 95% CI: -0.033-0.026, P = 0.818) and superior to UHR (AUC difference: 0.043, 95% CI: 0.019-0.067, P < 0.001) and THR (AUC difference: 0.035, 95% CI: 0.019-0.067, P = 0.047).ConclusionUAR was independently associated with MASLD and demonstrated significant diagnostic value, indicating that UAR could be a cost-effective biomarker to help identify high-risk individuals for MASLD.